Rescue Boat Design Utilizing Reused Plastic Bottles For Accident Preventation - Faturachman, Danny (2012)
Fiberglass layer of rescue boat has tendency to crack when hit by a heavy wave or involves in accident. As an alternative to this problem, waste plastic disposal is suggested to be reused in filling the displaced volume of the designed rescue boat. The main objective of this paper is to design a fiberglass rescue boat that has arrangement of bottles under the waterline section of the original boat design. The arrangement of waste plastic bottles will avoid the rescue boat from sinking if fiberglass layer of the boat happened to cracked. The design rescue boat will count on density and quantity of waste plastic bottles used at the core of the boat.